Asymmetric pass-through between oil prices and the stock prices of clean energy firms: New evidence from a nonlinear analysis - Baris Kocaarslan; Ugur Soytas (Energy Reports, 2019)
There is an ongoing debate on how oil prices affect the stock prices of clean energy companies. We contribute to this debate by questioning the possibility of asymmetric linkages between oil prices, interest rates, and the stock prices of clean energy and technology firms. Using a recently developed approach (nonlinear auto-regressive distributed lag (NARDL) model), we document that ignoring the presence of nonlinearities leads to misleading results. The analyses reveal significant asymmetric effects among the variables of interest. Our findings suggest that the impacts of positive and negative changes in the oil prices, interest rates and technology stock prices on clean energy stock prices substantially vary in the short-and long-run. More specifically, our results point out that the increased investments in clean energy stocks appear to be due to speculative attacks along with an increase in oil prices in the short-run. But, in the long-run, the increased oil price has a negative impact on clean energy stock prices and this impact is asymmetric. Last but not least, the results also emphasize the importance of business cycle fluctuations for the clean energy stock performance in the long-run. The implications of this paper are noteworthy for energy economists, policymakers, and investors in the energy and financial markets. JEL classification: C58, G10, Q42, Q43, Keywords: Asymmetries, Clean energy, Nonlinear ARDL (NARDL), Oil prices, Stock prices